Introduction to APOSOS project: 15 cm aperture electro-optical telescopes to track space objects. Issue 8 (15th April 2020) - Guo, Xiaozhong; Gao, Pengqi; Shen, Ming; Yang, Datao; Yu, Huanhuan; Liu, Tong; Li, Jiawei; Zhao, You
Abstract: Asia-Pacific ground-based Optical Space object Observation System (APOSOS) is an international cooperation project, which is initiated and supported by Asia-Pacific Space Cooperation Organization (APSCO). Currently, APOSOS consists of three Observation Nodes in Pakistan, Peru and Iran, and a Data and Operation Management Center in National Astronomical Observatories, Chinese Academy of Sciences. Each Observation Node is equipped with a dedicated 15 cm aperture refracting telescope, which is capable of real-time astrometric data reduction. APOSOS aims to develop a tracking network of space object to acquire accurate astrometric measurements of space objects owned by APSCO member states. In this paper, we present an overview of APOSOS's design and development. The APOSOS's detecting capability of tracking a space object is darker than 12 m in LEO or 16 m in GEO, the size of which is equivalent to a diameter of 10-cm class in LEO or meter class in GEO respectively. A parametric estimation model is setup to profile APOSOS's capability in different tracking missions, which is verified by experimental observations. Preliminary results of tracking observations of SLR satellites showed that RMS of APOSOS astrometric measurements in RA/DEC is better than 5 ″ .